Emergent ferromagnetism and unusual irreversible magnetoresistance in an intercalated van der Waals antiferromagnet - Zixin Zhai; Wenhao Liu; Xiaoyu Guo; Daniel J. Schulze; Ting-Wei Kuo; Nishkarsh Agarwal; Alex Stangel; Pramanand Joshi; J. Ping Liu; Liangzi Deng; Robert Hovden; Liuyan Zhao; et al. (Proceedings of the National Academy of Sciences, 2026)
Orthorhombic air-stable two-dimensional (2D) antiferromagnet (AFM) CrSBr has attracted much research interest lately thanks to its rich magnetic behaviors together with its remarkable electronic, excitonic, and polaritonic properties. Here, we report a reliable electrochemical intercalation method by inserting large tetrabutylammonium (TBA + ) ions into CrSBr layers. Magnetically, such intercalation efficiently suppresses the interlayer AFM and induces a ferromagnetic (FM) order with a much-enhanced transition temperature up to 200 K, nearly 70 K higher than the AFM onset of 132 K in pristine CrSBr. Electronically, the TBA + intercalation not only increases the electric conductivity of CrSBr, which is further enhanced by magnetic fields, but also introduces a giant negative irreversible magnetoresistance. This work demonstrates the tunable magnetic and electronic properties of CrSBr as well as their interplay, paving the way for advanced spintronic and magnetic memory devices.